Respuesta :

gmany

[tex]8(3a+6)=9(2a-4)\ \ \ \ |\text{use distributive property}\\\\(8)(3a)+(8)(6)=(9)(2a)-(9)(4)\\\\24a+48=18a-36\ \ \ \ |-48\\\\24a=18a-84\ \ \ \ |-18a\\\\6a=-84\ \ \ \ |:6\\\\\boxed{x=-14}[/tex]

First, distribute 8 to 3a and 6, and distribute 9 to 2a and -4

8(3a + 6) = 24a + 48

9(2a - 4) = 18a - 36

24a + 48 = 18a - 36

Isolate the a. Subtract 48 and 18a from both sides. (Note the equal sign. What you do to one side, you must do to the other.

24a (-18a) + 48 (-48) = 18a (-18a) - 36 (-48)

24a - 18a = -36 - 48

Simplify.

6a = -84

Isolate the a. Divide 6 from both sides

6a/6 = -84/6

a = -84/6

a = -14

-14 is your answer for a

hope this helps

Otras preguntas